2016
DOI: 10.1002/jcb.25638
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-Releasable Factors Stimulate the Expression of Granulocyte Colony-Stimulating Factor in Human Dermal Fibroblasts

Abstract: Interaction between keratinocytes and fibroblasts plays a critical role in maintaining skin integrity under both normal and pathological conditions. We have previously demonstrated that keratinocyte-releasable factors influence the expression of key extracellular matrix components, such as collagen and matrix metalloproteinases in dermal fibroblasts. In this study, we utilized DNA microarray analysis to examine the effects of keratinocyte-releasable factors on the expression of several cytokines in human derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
(58 reference statements)
1
18
0
Order By: Relevance
“…Keratinocytes and fibroblasts play important roles in wound healing 25 . To examine the effects of USC-Exos on keratinocyte and fibroblast function, we firstly determined whether USC-Exos could be internalized into these cells.…”
Section: Resultsmentioning
confidence: 99%
“…Keratinocytes and fibroblasts play important roles in wound healing 25 . To examine the effects of USC-Exos on keratinocyte and fibroblast function, we firstly determined whether USC-Exos could be internalized into these cells.…”
Section: Resultsmentioning
confidence: 99%
“…production of granulocyte-colony-stimulating factor (G-CSF) was identified in two of two in HD (17,50), while transforming growth factor (TGF)-β was found to be decreased in two of two studies (42,59). For connective tissue growth factor (CTGF), one study reported enhanced (26), and on other study decreased, production (35) by HD fibroblasts.…”
Section: -3-3 (Stratifin)mentioning
confidence: 99%
“…For connective tissue growth factor (CTGF), one study reported enhanced (26), and on other study decreased, production (35) by HD fibroblasts. Enhanced production of vascular endothelial growth factor (VEGF)-1, platelet-derived growth factor (PDGF)-1, hepatocyte growth factor (HGF), basic FGF (bFGF), monocyte (M)-CSF, granulocyte monocyte (GM)-CSF, and epimorphin were all found in single studies (17,23,26,55,60).…”
Section: -3-3 (Stratifin)mentioning
confidence: 99%
“…They secrete a broad spectrum of cytokines including proinflammatory cytokines, chemokines, and immunomodulatory cytokines and establish the local cytokine and chemokine milieu, which mediate multiple local and systemic consequences, such as migration of inflammatory cells, activation of immune responses, and proliferation and differentiation of keratinocytes and fibroblasts [ 48 50 ]. Keratinocytes can produce multiple cytokines such as IL-1, IL-6, IL-8, granulocyte-macrophage colony-stimulating factor, and transforming growth factor- (TGF-) α [ 49 , 51 , 52 ]. Keratinocytes also synthesize the C-X-C chemokines, including interferon gamma-induced protein 10 (IP-10), monocyte chemotactic protein-1 (MCP-1), and RANTES (regulated on activation, normal T cell expressed and secreted) [ 53 ].…”
Section: Tweak Enhances the Production Of Cytokines In Keratinocytmentioning
confidence: 99%